Development of Textbooks to Support Merdeka Curriculum Learning on Green Chemistry Material in Phase E - Feliska Amanda; Mawardi Mawardi; Okta Suryani (Jurnal Paedagogy, 2023)
This research aims to develop textbooks to support Merdeka curriculum learning on green chemistry material in phase E. The Plomp development model was utilized in the study method known as Educational Design study (EDR). A validation questionnaire sheet and a practicality questionnaire sheet were used to collect the data. The research results using Aiken's V formula showed that the five validator tests obtained a score in the valid category with a validity value of 88%. In contrast, the practicality test results for students had a value of 91% in the very practical category. The results for chemistry teachers had a value of 96% in the very practical category. According to the research data gathered, phase E-textbooks for the Merdeka curriculum fit under valid and practical categories.